Correction: Causal Inference for Spatial Cross-Sectional Data: A Geographical Convergent Cross Mapping Method Accounting for Spatial Autocorrelation - Kaixuan Zhang; Xiaoyu Hu; Yehua Sheng; Shifeng Yu; Lin Yang (Journal of Geovisualization and Spatial Analysis, 2026)

Seasonal variation of fish biodiversity in Xisha Islands based on dual-marker eDNA metabarcoding - Shengming Deng; Yuguo Ye; Min Liu; Bai-an Lin; Chengdan Ma; Yifeng Xu; Yongcan Zhou; Shifeng Wang; Weiliang Guo; Huilong Ou; Xiang Zhang; Jianlong Li (Marine Environmental Research, 2026)

Topical delivery of Lidocaine using spicules for local anesthesia - Chi Zhang; Ping Yang; Xueke Lin; Huijung Lai; Yi Liu; Shifeng Yu; Tszyam Liu; Ming Chen; Yongxiang Huang (Drug Delivery and Translational Research, 2026)

Metabolic Modelling Facilitates the Design of Synthetic Communities by Simplifying Natural Microbial Communities - Xinyu Lin; Shifeng Ding; Wanxin Li; Bingang Yang; Yahua Chen; Zhenguo Shen; Jiandong Jiang; Chen Chen; Xihui Xu (Environmental Microbiology, 2026)
Natural microbial communities generally have complex compositions and unclear metabolic interactions, posing constraints on their applications. Clarifying these intricate interactions within microbial communities is challenging for traditional experiment‐based methods. Here, we developed a simulation‐based approach to design synthetic communities (SynComs) by simplifying complex microbial communities through metabolic modelling. We constructed genome‐scale metabolic models (GSMMs) and curated them based on data obtained from straightforward experiments, ensuring these models precisely characterized metabolic features of each strain. By simulations utilizing multi‐strain metabolic models encompassing various strain combinations, we identified helper strains capable of enhancing the degradation efficiency of degrader strains and predicted optimal strain combinations that achieved a simplified community structure while maintaining high pollutant‐degrading efficiency. The simulations also unravelled cross‐feeding of glucosamine, amino acids and organic acids between the degrader and helper strains, which boosted the pollutant‐degrading efficiency of SynComs. Furthermore, helper strains rapidly degraded the toxicant intermediate, thereby alleviating its inhibitory effect on degrader strains. These predictions were further verified experimentally, demonstrating the accuracy and feasibility of metabolic model‐based simulations. Our study establishes a framework for designing simplified SynComs without sacrificing degradation efficiency and highlights the often‐underestimated role of microbial interactions in biodegradation.

Landslide-terrace interaction mechanisms of two rapid loess landslide cases: insights from MPM modeling - Wei Shen; Jianchao Chen; Yuqi Chen; Shifeng Lin; Denghai Liu; Tonglu Li (Landslides, 2026)

Effects of Temperature on Artificial Breeding and Early Development of Osteochilus salsburyi - Yang Yang; Yutian Gong; Guoliang Li; Qi Su; Shifeng Guan; Haitao Zheng; Lin Xu; Feng Chen; Xuan Zhao; Zhiming Zhang (Fishes, 2026)
To determine the optimal water temperature range for artificial breeding and early development of Osteochilus salsburyi, six water temperature gradients (14, 18, 22, 26, 30, and 34 °C) were set to systematically investigate the effects of water temperature on artificial reproduction efficiency, embryonic development, the morphology of newly hatched larvae, larval growth performance, and the timing of organ development in O. salsburyi. The results showed that the spawning induction rate of O. salsburyi reached 100% at 14–30 °C. The fertilization rate and hatching rate peaked at 18–22 °C, and no fertilization was completed at 34 °C. The malformation rates of embryos and larvae showed a U-shaped change, with the lowest malformation rate at 18 °C, and the teratogenic effect of high-temperature stress was more significant. The embryonic development rate was significantly negatively correlated with water temperature, and the development duration was significantly shortened with increasing water temperature. Embryonic development was arrested and all embryos died at 34 °C, while hatching could be completed at 14 °C but with an excessively long cycle. The morphological indicators of newly hatched larvae showed differentiated sensitivity to water temperature; total length, pre-anal length, and body height were highly sensitive indicators, and larvae exhibited balanced and robust morphological development at 18–22 °C. The larval survival rate first increased and then decreased with increasing water temperature, reaching the highest rate at 22–26 °C. The absolute growth increment, relative growth increment, and specific growth rate (SGR) continued to increase with increasing water temperature. The timing of larval organ differentiation and behavioral development was significantly advanced with increasing water temperature. Late organ development of larvae was blocked at 14 °C, only early development was completed at 34°C, and the internal and external organs of larvae developed completely and in an orderly manner at 18–30 °C. In summary, the optimal water temperature for artificial breeding and early development of O. salsburyi is 18–26 °C, among which 18–22 °C is the best for artificial reproduction and 22–26 °C is optimal for larval rearing. The results can provide a scientific basis for the precise regulation of water temperature in large-scale seedling production of O. salsburyi.

Causal Inference for Spatial Cross-Sectional Data: A Geographical Convergent Cross Mapping Method Accounting for Spatial Autocorrelation - Kaixuan Zhang; Xiaoyu Hu; Yehua Sheng; Shifeng Yu; Lin Yang (Journal of Geovisualization and Spatial Analysis, 2026)

Usage patterns and system dynamics of car-sharing in Chinese cities: Insights from a data-driven framework - Hongjie Wang; Xia Luo; Junfeng Chen; Qiming Su; Yaodong Wang; Shifeng Gong; Lin Qu (Sustainable Cities and Society, 2025)

A grid search-based optimal trajectory planning approach for automatic berthing of underactuated unmanned surface vehicles - Shidi Wu; Shifeng Ding; Lin Geng; Zihan Chen; Sen Han; Li Zhou (Ocean Engineering, 2025)

Cross-sectional and Longitudinal Associations Between Metal Mixtures and Serum C3, C4: Result from the Manganese‑exposed Workers Healthy Cohort - Sencai Lin; Junxiu He; Yinghua Zhou; Yu Bao; Xiuming Feng; Hong Cheng; Haiqing Cai; Sihan Hu; Lin Wang; Yuan Zheng; Mengdi Zhang; Qinghua Fan; et al. (Biological Trace Element Research, 2025)

A novel BiVO4/vermiculite Z-scheme heterojunction with enhanced removal rate of dyes through adsorption photodegradation synergistic mechanism - Lin Han; Liying Wen; Xiaoju Yue; Jinnong Wang; Yue Liu; Yuanhao Wang; Shifeng Wang (Journal of Water Process Engineering, 2024)

A poly (L-glutamic acid)-based porous scaffold with controllable and sequential release of kartogenin for enhanced cartilage regeneration - Xi Yu; Feng Lin; Yaling Zhuang; Shifeng Yan; Kunxi Zhang; Wenguo Cui; Jingbo Yin (Chemical Engineering Journal, 2024)

Lead-rivet strategy of growing perovskite nanocrystals for excellent toxicity inhibition and spinning application - Hanlong Wang; Shifeng Zhu; Jiaoyue Sheng; Feihong Gao; Lei Yang; Xili Hu; Francisco Fernández-Martínez; Longhui Lin; Chaoyu You; Dongming Xing (Journal of Hazardous Materials, 2024)

Risk of papillary thyroid carcinoma and nodular goiter associated with exposure to semi-volatile organic compounds: A multi-pollutant assessment based on machine learning algorithms - Fei Wang; Yuanxin Lin; Jianing Xu; Fugui Wei; Simei Huang; Shifeng Wen; Huijiao Zhou; Yuwei Jiang; Haoyu Wang; Wenlong Ling; Xiangzhi Li; Xiaobo Yang (Science of The Total Environment, 2024)

Spatial convolutional self-attention-based transformer module for strawberry disease identification under complex background - Gaoqiang Li; Lin Jiao; Peng Chen; Kang Liu; Rujing Wang; Shifeng Dong; Chenrui Kang (Computers and Electronics in Agriculture, 2023)

Efficiency Assessment of Hazardous Waste Disposal in EU Countries: A Three-Stage Super-Efficiency Data Envelopment Analysis Model - Meng Ye; Xuedong Liang; Shifeng Lin; Huirong Lin; Fumin Deng (Environmental Management, 2022)

Nitrogen Fertilization and Precipitation Affected Wheat Nitrogen Use Efficiency and Yield in the Semiarid Region of the Loess Plateau in China - Jie Ren; Aixia Ren; Wen Lin; Hafeez Noor; Shahbaz Khan; Shifeng Dong; Min Sun; Zhiqiang Gao (Journal of Soil Science and Plant Nutrition, 2022)

Selenium-Alleviated Testicular Toxicity by Modulating Inflammation, Heat Shock Response, and Autophagy Under Oxidative Stress in Lead-Treated Chickens - Size Wang; Lulu Hou; Min Wang; Rui Feng; Xu Lin; Shifeng Pan; Qian Zhao; He Huang (Biological Trace Element Research, 2021)

Discovery of a naturally-occurring allele of eIF4E1.S in Nicotiana tabacum and development of a co-dominant marker - Shifeng Lin; Ralph E. Dewey; Rengang Wang; Jing Yu; Mingjin Long; Jie Zhang; Shizhou Yu; Jishun Zhang; Zili Wang; Xueliang Ren (Euphytica, 2021)

Chinese construction industry energy efficiency analysis with undesirable carbon emissions and construction waste outputs - Xuedong Liang; Shifeng Lin; Xueyao Bi; Enfan Lu; Zhi Li (Environmental Science and Pollution Research, 2021)

Muscovy Duck Reovirus Infection Disrupts the Composition of Intestinal Microbiota in Muscovy Ducklings - Xiuqin Chen; Min Zheng; Meiqing Huang; Shifeng Xiao; Fengqiang Lin; Shaoying Chen; Shilong Chen (Current Microbiology, 2020)

Isolation and characterization of a distinct duck-origin goose parvovirus causing an outbreak of duckling short beak and dwarfism syndrome in China - Shilong Chen; Shao Wang; Xiaoxia Cheng; Shifeng Xiao; Xiaoli Zhu; Fengqiang Lin; Nanyang Wu; Jinxiang Wang; Meiqing Huang; Min Zheng; Shaoying Chen; Fusong Yu (Archives of Virology, 2016)